Discrete wavelet packet transform based controller for liquid level system and its performance analysis. (February 2017) - Paul, Rimi; Sengupta, Anindita
Highlights: A real time linear first order RC plant, analogous to the lab scale LLS is taken. The wavelet packet controller (DWPTPI) is developed. In real time, noise may appear due to sensor, connecting wires, parametric changes. The performance of PC based controllers (DWPTPI, DWTPI and PI) are compared. This new and fast controller has also been applied for second order plant. Abstract: A new controller based on discrete wavelet packet transform (DWPT) for liquid level system (LLS) has been presented here. In this proposed controller, packet transform is used to decompose the error signal into different frequency nodes at various scales which represents many underlying phenomena such as process dynamics, noise and disturbances. These coefficients are scaled by their respective gains and then added together to generate the control signal. NI DAQ device is used to interface between the PC based controllers simulated in NI LABVIEW software to the real time RC plant analogous to LLS and a second order RLC plant. The performance of this controller has been studied and compared to the PI controller. From hardware results, this controller is shown to perform better than both the discrete wavelet transform (DWT) based proportional integral controller and PI controller. Also, it can handle noise more efficiently.